Recepção radiofônica: o rádio no cotidiano de uma comunidade rural na Amazônia paraense - RODRIGUES, Manoel Ednaldo (Universidade Federal do Pará, 2017)
The focus of this paper was to investigate by means of radio listening the importance of radio in everyday life of the residents of Vila Brazil, in Rio Arapiuns region in Santarém - Pará Theoretical and methodological construction was based on the Latin American cultural studies proposed by Jesús Martín - Barbero, Néstor García Canclini and Guillermo Orozco - Gómez as a theoretical orientation to the study of communication. Leaving contributions of these researchers and Brazilian authors, among others, Ana Carolina Escosteguy, Nilda Jacks, Itânia Maria Gomes, Mauro Wilton de Sousa, Luiz Artur Ferraretto, discusses the concept of radio reception about the importance of radio in a rural community Amazon in Pará, in the region of rivers, one of the peculiarities found in the geographical formation of the Amazon. The reception research was conducted in six visits to the community in the months of July, September, October and November 2013, totaling six weeks in locality, interspersed, and exploratory visits before to the start date of the activities in the field. In this process, the corpus consisted of study and analyzed a set of information obtained from interviews, questionnaires and other approaches such as participant observation and oral history, through testimonies of community. Brazil village has 329 residents, of whom 219 participated in the study. The research was conducted on three groups - adolescents, adults and the elderly - to stand up information regarding the importance of radio in everyday life of the residents of Vila Brazil. It was found that the radio still has relevance to the community in various organizational segments importance with the irradiation of, among others, news, educational, sports, labor and religious content as an integral part of the culture of a traditional Catholic community, even considering the strong presence of other mediations. It was also found that television is present in the community and that the night program plays a role as a unifying element in the family, but the radio is still the medium that streamlines the daily lives of residents, indicating specific elements to understanding the Radio contemporaneity and its role as one of the most important means of communication in the Amazon. The existing communication media in the community are the radio (battery and electricity), television (via satellite) and the mobile phone operator Vivo, accessed through makeshift antennas, working precariously.